The Pattern of Iodine Food Source Intake in Early Adolescents in Junior High School in Jatinangor - Siti Nur Fatimah; Che Wan Nurdamia; Faisal Faisal (Althea Medical Journal, 2019)
Background: Iodine is one of the essential micronutrients for normal growth, development, and metabolism throughout life. Studies about the pattern of iodine food source intake in Indonesia are lacking. The aim of this study was to assess the current pattern of iodine food source intake among early adolescents.Methods: This was a cross-sectional study, the pattern of iodine food source intake in early adolescents aged 11–14 years attending Junior High School in Jatinangor Sumedang, Indonesia was assessed from September to October 2014, by validated food frequency questionnaire (FFQ). Eating patterns were divided into four categories based on Indonesian Recommended Dietary Allowance (RDA).Results: The average iodine daily intake of the subjects was 356.27 mcg. The highest frequency of the iodine intake category was adequate in students aged 11–12 years old (100%), compared to aged 13–14 years old (79.2%).Conclusions: The daily iodine intake in Junior High School students is sufficient. Further assessment in areas elsewhere in West Java needs to be conducted to have a better picture of the pattern of iodine food source intake in adolescents.